2015
DOI: 10.1007/s12517-015-1960-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-climatic aspects of Indus River flow propagation

Abstract: One of the world's largest irrigation networks of Pakistan is based on Indus River System. These networks face serious scarcity of water in 1 year, and agricultural land destructive disastrous floods in the other. To understand the physical basis of statistical variations in space and time in the river flow, this study assesses the reasons governing the system. Therefore, time series analysis of the mean monthly river flow data is performed. The results show strong linear and seasonal behaviour among the river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Recent studies reported that the spatiotemporal variability of temperature and precipitation in northern Pakistan has significant effects on water availability of the Indus River network (Hartmann and Buchanan, 2014;Ahmad et al, 2015). The Indus River and its tributaries face water scarcity in 1 year and catastrophic floods in the other year (Ashiq et al, 2010;Hassan and Ansari, 2015). The country has faced severe floods and drought disasters in the last few decades, which could be the results of these phenomena.…”
Section: Elevation-dependent Warmingmentioning
confidence: 99%
“…Recent studies reported that the spatiotemporal variability of temperature and precipitation in northern Pakistan has significant effects on water availability of the Indus River network (Hartmann and Buchanan, 2014;Ahmad et al, 2015). The Indus River and its tributaries face water scarcity in 1 year and catastrophic floods in the other year (Ashiq et al, 2010;Hassan and Ansari, 2015). The country has faced severe floods and drought disasters in the last few decades, which could be the results of these phenomena.…”
Section: Elevation-dependent Warmingmentioning
confidence: 99%
“…The intensity and annual pattern (illustrates the twelve-month cycle) of temperature of Chitral, Gilgit, Skardu (Fig. 4 & 5b) supports the regional regular snow-glacier melts runoff [15]. These seasonal/annual variations of rainfall and temperature influence the regional river flow can be analysed by ACF and PACF analyses.…”
Section: Methodsmentioning
confidence: 53%
“…6a). In comparison with the same of the Indus river flow at Tarbela station [15] shows sustainable roll off pattern (Fig. 9), ( [15] the reference there in Fig.…”
Section: Proficiency Of the Modelmentioning
confidence: 71%
See 1 more Smart Citation
“…The arena of problems like correct assessment, proper storage, reliable control and judicious distribution of existing water masses among various provinces/regions within Pakistan is properly encompassed by technical research and mathematical modelling. Keeping in view the preliminary local climatic analyses as presented in Hassan and Ansari (2015) and linear and nonlinear analyses performed in Hassan and Ansari, (2010), and Hassan (2011) [1][2][3][4][5], this paper assess the impact of climatic parameters (Temperature & Rainfall) on mean 10daily river flow (TDF) along the Indus River.…”
Section: Introductionmentioning
confidence: 99%